THE INFLUENCE OF THIRD PARTY FUNDING, CAPITAL ADEQUACY RATIO AND NON PERFORMING FINANCING ON COMPANY PROFITABILITY - Elwisam; Melati; Muhani; Kumba Digdowiseiso (CV. Radja Publika, 2024)
This research aims to investigate the influence of third party funds, Capital Adequacy Ratio (CAR), and Non-Performing Financing (NPF) on company profitability in the context of Islamic banking and finance. Using a Systematic Literature Review (SLR) approach, this research identified 10 relevant accredited national journals via Google Scholar and the